The External Balance Assessment Methodology : 2018 Update - Cubeddu, Luis (IMF Working Papers; Working Paper, 2019)
The assessment of external positions and exchange rates is a key mandate of the IMF. This paper presents the updated External Balance Assessment (EBA) framework-a key input in the conduct of multilaterally-consistent external sector assessments of 49 advanced and emerging market economies-following the two rounds of refinements adopted since the framework was introduced in 2012 (as described in Phillips and others, 2013). It also presents new complementary tools for shedding light on the role of structural factors in explaining external imbalances and assessing potential biases in the measurement of external positions. Remaining challenges and areas of future work are also discussed.